2017
DOI: 10.1155/2017/1645828
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Oxidized Linoleic Acid Modulates Plasma Lipids beyond Triglycerides Metabolism

Abstract: Introduction Triglyceride (TG) is an independent risk factor for coronary heart disease. Previous work has shown that short-term supplementations of mouse chow with oxidized linoleic acid (OxLA) significantly reduce the level of plasma triglycerides. Study Objective This study aims to determine the effects of longer-term supplementation of mouse chow with various concentrations of oxidized linoleic acid (OxLA) on plasma triglycerides. Study Design The study consisted of forty C57BL/6 wildtype mice divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…No significant difference was seen between both treated groups, showing the comparable effect of both treatments in increasing HDL uptake. Previous studies have reported that treatment with LA enhanced HDL levels in human [29,30] and animal [44] studies. In this study, increased HDL uptake in the LA-treated HepG2 cells was attributed to increased mRNA expression of the SR-BI gene.…”
Section: Discussionmentioning
confidence: 90%
“…No significant difference was seen between both treated groups, showing the comparable effect of both treatments in increasing HDL uptake. Previous studies have reported that treatment with LA enhanced HDL levels in human [29,30] and animal [44] studies. In this study, increased HDL uptake in the LA-treated HepG2 cells was attributed to increased mRNA expression of the SR-BI gene.…”
Section: Discussionmentioning
confidence: 90%
“…This could be due to the LCFAs being major constituents of larger lipid molecules such as triglycerides and cholesterol esters within the liver and the blood. 27 28 The fatty acids in the livers of group A mice had significant higher concentrations than the concentration in the livers of the P group controls while the concentrations in the B group were statistically significantly less than the controls. This may be due to a dose dependent mechanism of oxidized LA associated with the biosynthesis and catabolism of fatty acids in the liver.…”
Section: Discussionmentioning
confidence: 92%
“…The metabolic effect(s) of species such as oxidised triglycerides have not yet been characterised in infants. There is reasonable evidence to warrant the assumption that these compounds can have possible down-stream biological activity [50,51], for example, though agonism of PPAR receptors by oxidised fatty acids [52].…”
Section: Discussionmentioning
confidence: 99%